Elucidation of the mechanism of enzymatic browning inhibition of the sap from oil palm trunk by chemical method - Mohd.Khairul Anuar, Samsudin (2010)
Objective of this research is to find and explain how chemical prevents enzymatic browning to occur. There are three stages in the experiment for this research, first is obtain the oil palm sap and let it react with air and observe the changes of the color of oil palm sap. Second stage is obtain the oil palm sap sample and test it with selected chemical which is Ascobic Acid (AA), Citric Acid (CA), L-cystien (LC), Sodium Chlorite (SC) and Catechol (CAT). The last stages of this research is analysis the oil palm sap, observation in color changes of the sap for 12 hour and 24 hour, measures absorbance from the UV range of the oil palm sap and using FTIR. Since browning reaction initiated by the enzymatic oxidation of Monophenol to 0-Diphenol than Quinines, non enzymatic browning polymerization of Quinines lead to the formation of the pigmen that cause change in color of the sap. Result of the first stages of the experiment show the enzymatic browning occurs to oil palm sap with change of color of sap within 24 hour. For second stage of the experiment show AA, CA and LC show the positive result which the lowest concentration of selected chemical give change of sap color and high concentration of selected chemical does not change the original color of the sap after 24 hour. CAT and SC show the negative result which the highest concentration of CAT changes the sap color darker and highest concentration of SC change the actual sap color to another color. Result from the analysis using FTIR and Uv- Vis analysis show there are possibility all of the sample have phenolic compound that can cause the enzymatic browning .When comparing result with control measure of FTIR with FTIR of the inhibitor, result of ascorbic acid is most preferable to be inhibition of browning agent for oil palm sap.